Cannabinoids induce latent sensitization in a preclinical model of medication overuse headache. (January 2020) - Kopruszinski, Caroline M; Navratilova, Edita; Vagnerova, Barbora; Swiokla, Juliana; Patwardhan, Amol; Dodick, David; Porreca, Frank
Aim: Evaluation of cannabinoid receptor agonists in a preclinical model of medication overuse headache. Methods: Female Sprague Dawley rats received graded intraperitoneal doses of WIN55, 212-2 or Δ-9-tetrahydrocannabinol (Δ-9-THC). Antinociception (tail-flick test), catalepsy and hypomotility (open field test) and impairment of motor function (rotarod test) were assessed to establish effective dosing. Rats were then treated twice daily with equianalgesic doses of WIN55, 212-2 or Δ-9-THC, or vehicle, for 7 days and cutaneous tactile sensory thresholds were evaluated during and three weeks following drug discontinuation. Rats then received a one-hour period of bright light stress (BLS) on two consecutive days and tactile sensory thresholds were re-assessed. Results: WIN55, 212-2 and Δ-9-THC produced antinociception as well as hypomotility, catalepsy and motor impairment. Repeated administration of WIN55, 212-2 and Δ-9-THC induced generalized periorbital and hindpaw allodynia that resolved within 3 weeks after discontinuation of drug. Two episodes of BLS produced delayed and long-lasting periorbital and hindpaw allodynia selectively in rats previously treated with WIN55, 212-2, and Δ-9-THC. Interpretation: Cannabinoid receptor agonists including Δ-9-THC produce a state of latent sensitization characterized by increased sensitivity to stress, a presumed migraine trigger. Overuse of cannabinoids including cannabis may increase the risk of medication overuse headache in vulnerable individuals.